PRE-SERVICE TEACHERS’ KNOWLEDGE AND OPINION ABOUT STEM EDUCATION IN PRESCHOOL - BÁLINT-SVELLA, Éva; ZSOLDOS-MARCHIȘ, Iuliana (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2022)
In recent years, the focus of many researches has been on STEM activities and their application possibilities. The current research examines the opinion and experience of 85 Primary and Preschool Pedagogy specializations students regarding the use of STEM activities in kindergarten. The research tool was a questionnaire that included 18 questions: 5 questions with demographic data, 3 questions on how to integrate different experiential fields in pre-school activities, and 10 questions related to students’ knowledge and experience about STEM activities. The results show that students integrate different experiential fields. More than half of the respondents are unfamiliar with the term STEM and don’t have any personal experiences with STEM. These results highlight the necessity of integrating STEM Education in pre-service and in-service teachers training. The results also present students’ opinion about the essence and opportunities of STEM Education, and the cognitive, emotional, social, and physical skills/abilities most developed by STEM. Received: 2022 March 05; Revised: 2022 March 25; Accepted: 2022 March 28; Available online: 2022 May 5; Available print: 2022 May 30 The authors have equal contribution.